Assessing the effects of repeated handling on the physiology and condition of semi‐precocial nestlings. (17th August 2016) - Watson, Hannah; Bolton, Mark; Heidinger, Britt J.; Boner, Winnie; Monaghan, Pat
Abstract : Repeated exposure to elevated levels of glucocorticoids during development can have long‐term detrimental effects on survival and fitness, potentially associated with increased telomere attrition. Nestling birds are regularly handled for ecological research, yet few authors have considered the potential for handling‐induced stress to influence hormonally mediated phenotypic development or bias interpretations of subsequent focal measurements. We experimentally manipulated the handling experience of the semi‐precocial nestlings of European Storm Petrel Hydrobates pelagicus to simulate handling in a typical field study and examined cumulative effects on physiology and condition in late postnatal development. Neither baseline corticosterone (the primary glucocorticoid in birds), telomere length nor body condition varied with the number of handling episodes. The absence of a response could be explained if Storm Petrels did not perceive handling to be stressful or if there is dissociation of the hypothalamic–pituitary–adrenal axis from stressful stimuli in early life. Eliciting a response to a stressor may be maladaptive for cavity‐dwelling young that are unable to escape or defend themselves. Furthermore, avoiding elevated overall glucocorticoid exposure may be particularly important in a long‐lived species, in which accelerated early‐life telomere erosion could impact negatively upon longevity. We propose that the level of colony‐wide disturbance induced by investigator handling of young could be important in underlining species‐specific responses. Storm Petrel nestlings appear unresponsive to investigator handling within the limits of handling in a typical field study and handling at this level should not bias physiological and morphological measurements.